2019
DOI: 10.1093/reseval/rvz009
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a short multidisciplinary research performance questionnaire (SMRPQ)

Abstract: Research is often specialized and varies in its nature between disciplines, making it difficult to assess and compare the performance of individual researchers. Specific qualitative and quantitative indicators are usually complex and do not work equally well for different research fields. Therefore, the aim of the present study was to develop an economical questionnaire that is valid across disciplines. We constructed a Short Multidisciplinary Research Performance Questionnaire (SMRPQ), with which researchers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…In accord with prior research (see Daumiller et al, 2019, for an overview), we found strong autoregressive effects for the examined constructs. This finding underpins the high stability of achievement and self-concept in research and teaching over time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accord with prior research (see Daumiller et al, 2019, for an overview), we found strong autoregressive effects for the examined constructs. This finding underpins the high stability of achievement and self-concept in research and teaching over time.…”
Section: Discussionsupporting
confidence: 90%
“…Achievements. We measured research achievement using three items from Daumiller et al (2019), in which the faculty members indicated whether they had published more publications, published higher-quality publications, or obtained more external funding during the last six months compared to faculty members in the same field and with the same academic status. The faculty members answered these items on a visual analog scale with sliders from 0 to 99 (e.g., "In the last six months, I have published more publications than ___% of the other researchers of my status in my community").…”
Section: Measurementsmentioning
confidence: 99%
“…Second, we focused on a self-report measure to be used in nomothetic research. However, beyond such research, this approach is not appropriate for high stakes testing as it can be easily manipulated (see Daumiller, Siegel, et al, 2019), or for when individual dimensions of teaching quality are of interest. However, for teaching quality as a whole, we consider teacher self-reports as a valid indicator and find that, besides their face and predictive validity, they also converge well with student reports.…”
Section: Discussionmentioning
confidence: 99%
“…We used data from a larger research project in which student assessments of teaching quality were considered as consequences of faculty motivations (Daumiller, Siegel, et al, 2019). Students of the participating faculty members were asked to assess teaching quality across multiple sessions and courses, allowing for fine-grained insights.…”
Section: Methodsmentioning
confidence: 99%
“…Development and implementation of vocational educational programs. The central place in these issues is occupied by the tasks associated with developing and implementing educational programs for vocational education [1,2]. They are at the heart of any quality development, and the educational environment is no exception.…”
mentioning
confidence: 99%